2003
DOI: 10.1042/bj20030510
|View full text |Cite
|
Sign up to set email alerts
|

Role of flanking sequences and phosphorylation in the recognition of the simian-virus-40 large T-antigen nuclear localization sequences by importin-α

Abstract: The nuclear import of simian-virus-40 large T-antigen (tumour antigen) is enhanced via phosphorylation by the protein kinase CK2 at Ser112 in the vicinity of the NLS (nuclear localization sequence). To determine the structural basis of the effect of the sequences flanking the basic cluster KKKRK, and the effect of phosphorylation on the recognition of the NLS by the nuclear import factor importin-alpha (Impalpha), we co-crystallized non-autoinhibited Impalpha with peptides corresponding to the phosphorylated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 51 publications
12
100
0
Order By: Relevance
“…Co-crystal structures of both S. cerevisiae and M. musculus importin-a have been solved in complex with various NLS peptides (52)(53)(54)(55)(56)(57)(58)(59). The three-dimensional structures reveal that NLS peptides bind specifically in two binding grooves created by flexible armadillo (ARM) motifs in the central domain of importin-a (54, 55).…”
Section: Classical Nls Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-crystal structures of both S. cerevisiae and M. musculus importin-a have been solved in complex with various NLS peptides (52)(53)(54)(55)(56)(57)(58)(59). The three-dimensional structures reveal that NLS peptides bind specifically in two binding grooves created by flexible armadillo (ARM) motifs in the central domain of importin-a (54, 55).…”
Section: Classical Nls Sequencesmentioning
confidence: 99%
“…These grooves interact specifically with the basic, positively charged residues of the cNLS through hydrophobic and electrostatic interactions (3). Between these two binding pockets is a linker-binding region that interacts with the NLS peptide backbone (52,55,57). Changes to specific residues within each of these three regions of importin-a disrupt the nuclear localization and binding of cNLScargoes to importin-a (60,61).…”
Section: Classical Nls Sequencesmentioning
confidence: 99%
“…Phosphorylation within or around an NLS is the usual strategy for the regulated nuclear transport of a protein (4,(10)(11)(12)(13). It has been shown that acidic amino acids adjacent to the basic core of an importin-␣-dependent NLS inhibit the NLS activity (5,14).…”
mentioning
confidence: 99%
“…Flexible and contiguous NLS regions within target proteins ranging in length from 5 to 25 amino acids (40) are typical. Crystal structures of NLS peptides bound to importin-␣ reveal extended backbone conformations (43)(44)(45)(46), similar to the putative NLS region of the EcCdtB crystal structure. In the EcCdtB crystal structure, the formation of helix E results in the NLS Arg 191 -Arg 192 side chains being extended into the solvent (43) (Figs.…”
Section: Distinct Eccdtb Solution and Crystal States Provide Insightsmentioning
confidence: 88%